Soil spiders (Arachnida: Araneae) in native and reforested araucaria forests - Pereira J.M. (2020)
© 2021, Scientia Agricola. All rights reserved.Spiders are part of the soil biodiversity, considered fundamental to the food chain hierarchy, directly and indirectly influencing several services in agricultural and forest ecosystems. The present study aimed to evaluate the biodiversity of soil spider families and identify which soil properties influence their presence, as well as proposing families as potential bioindicators. Native forest (NF) and reforested sites (RF) with Araucaria angustifolia (Bertol.) Kuntze were evaluated in three regions of the state São Paulo, both in the winter and summer. Fifteen soil samples were collected from each forest to evaluate the biological (spiders and microbiological), chemical and physical soil properties, in addition to properties of the litter (dry matter and C, N and S contents). For soil spiders, two sampling methods were used: pitfall traps and soil monoliths. In total, 591 individuals were collected, and distributed in 30 families, of which 306 individuals (22 families) came from pitfall traps and 285 individuals (26 families) from monoliths. Only samples obtained by the monolith method revealed seasonal differences in the mean density and richness of spiders between NF and RF. Canonical discriminant analysis showed the separation of these forests of Araucaria. Principal Component Analysis demonstrated the correlation of a number of spider families with certain soil properties (organic carbon, basal respiration, metabolic quotient, litter carbon, total porosity, bulk density and soil moisture). We identified 10 families (Anapidae, Corinnidae, Dipluridae, Hahniidae, Linyphiidae, Lycosidae, Nemesiidae, Palpimanidae, Salticidae, Scytodidae) that contributed most to separating native forest from the replanted forest, indicating the possibility of the spiders being used as bioindicators.